PENANGANAN SURAT MASUK DAN SURAT KELUAR PADA INSTANSI PEMERINTAH SEBAGAI BENTUK KOMUNIKASI BISNIS - Yunidyawati Azlina (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2022)
Business communication covers all activities related to business activities including correspondence. Correspondence includes those relating to the handling of correspondence, including incoming and outgoing letters. The development of correspondence is currently very rapid, especially in the handling of letters, both incoming and outgoing mail. This happens because they are increasingly aware of the importance of incoming and outgoing letters in activities carried out in government and private offices. Activities will not run and develop properly without having a relationship or communication between each other or with other parties. The purpose of this study was to determine the handling of incoming and outgoing mail, the obstacles faced and how to overcome the obstacles, at the Government Service Office. The method used in this research is descriptive qualitative analysis. While the data collection techniques used are observation and documentation. The results showed that the handling of incoming and outgoing letters can be said to be good in accordance with the procedures and the obstacles in handling incoming and outgoing letters are the lack of place or space for important letters and handling of letters is still a little slow, sometimes old letters reach the recipient. concerned, the Head of Service who is sometimes rarely in place so that the signing of the letter becomes late. However, the handling of incoming and outgoing letters at the Government Service Office can be said to be good and in accordance with the procedures set at the Government Service.